Effect of thinning on stem form and wood characteristics of teak (Tectona grandis) in humid tropical site in Costa Rica - Pérez, D.; Kanninen, M. (2005)
The aim of the study was to evaluate the effects of thinning intensity on wood properties, such as heartwood proportion, wood density, and stem form of teak (Tectona grandis L.f.). The thinning trial was established on a teak plantation in a humid tropical site in northern Costa Rica. The moderate and heavy thinnings yielded the highest percentage of heartwood volume (25 to 30% of total stem volume). The differences between stem form factors under different treatments were not statistically significant after separating thinning effects from timing effects. Both the highest (>0.65 g cm-3 (grams per cubic centimeter)) and the lowest (<0.50 g cm-3) wood density values were observed under light thinnings, making it difficult to establish a relationship. Large variations in wood properties found under different thinning regimes suggest that early stages teak stands can be managed under different thinning programs without negatively affecting the quality of wood under humid tropical conditions.